MANGANESE MINERALISATIONS AT THE BASE OF MIOCENE SEDIMENTS IN NORTHERN SARDINIA (ITALY) - Fadda, S.; Fiori, M.; Pretti, S.; Valera, P. (Bulletin of the Geological Society of Greece, 2010)
During the eastward drift of the Palaeozoic-Mesozoic block formed by Sardinia and Corsica in the Oligocene-Miocene, calc-alkaline volcanism developed mostly in the western part of the island. Most Tertiary metallogenic phoenomena are related to hydrothermal activity associated with this volcanism. Following volcanic and related hydrothermal activity, sediments were deposited during the Oligocene-Miocene as a consequence of a marine transgression. The basal part of this series is clastic and includes elements derived from erosion of unaltered volcanics as well as hydrothermally altered rocks and hydrothermal vein quartz. Inside the Tertiary volcanics manganese ore-minerals occur as nodules, veinlets, and stockworks and mainly include Mn and Fe oxides; quartz in different forms is the most common gangue mineral. The mineralisations at the contact between volcanics and Miocene sediments are the most homogeneous, the ore-minerals occur in the cement, but also as fairly continuous thin beds, nodules and veinlets containing pyrolusite, frequent ramsdellite, less frequent manganite, psilomelane, cryptomelane-manjiroite, rare ranciéite, and todorokite. The nature of the ore-bearing beds indicate a near-shore clastic environment along the ancient coastal lines of the Miocene sea. Genetic considerations point to a supergenic transport and redeposition after erosion of primary dispersion and residual concentrations of Mn in the volcanics.